Conductance quantisation in patterned gate In0.75Ga0.25As structures up to 6 × (2e2/h). (21st January 2019) - Gul, Y; Creeth, G L; English, D; Holmes, S N; Thomas, K J; Farrer, I; Ellis, D J; Ritchie, D A; Pepper, M
Abstract: We present electrical measurements from In0.75 Ga0.25 As 1D channel devices with Rashba-type, spin–orbit coupling present in the 2D contact regions. Suppressed backscattering as a result of the time-reversal asymmetry at the 1D channel entrance results in enhanced ballistic transport characteristics with clear quantised conductance plateaus up to 6  ×  (2 e 2 / h ). Applying DC voltages between the source and drain ohmic contacts and an in-plane magnetic field confirms a ballistic transport picture. For asymmetric patterned gate biasing, a lateral spin–orbit coupling effect is weak. However, the Rashba-type spin–orbit coupling leads to a g -factor in the 1D channel that is reduced in magnitude from the 2D value of 9 to ~6.5 in the lowest subband when the effective Rashba field and the applied magnetic field are perpendicular.